2005
DOI: 10.1074/jbc.m501281200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Differences in Promoter DNA Melting by Thermus aquaticus and Escherichia coli RNA Polymerases

Abstract: Formation of strand-separated, functional complexes at promoters was compared for RNA polymerases from the mesophile Escherichia coli and the thermophile Thermus aquaticus. The RNA polymerases contained sigma factors that were wild type or bearing homologous alanine substitutions for two aromatic amino acids involved in DNA melting. Substitutions in the A subunit of T. aquaticus RNA polymerase impair promoter DNA melting equally at temperatures from 25 to 75°C. However, homologous substitutions in 70 render E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…Remarkably, the effect of the G424R substitution on promoter opening has been observed only in combination with substitutions in subregions 2.1 and 2.2. In agreement with this, it has been reported that a single complementary R247G substitution in T. aquaticus A did not affect promoter binding by T. aquaticus RNAP holoenzyme (19). At the same time, this substitution enhanced RNAP interactions with single-stranded DNA, suggesting a role for this amino acid in promoter opening (19).…”
supporting
confidence: 70%
“…Remarkably, the effect of the G424R substitution on promoter opening has been observed only in combination with substitutions in subregions 2.1 and 2.2. In agreement with this, it has been reported that a single complementary R247G substitution in T. aquaticus A did not affect promoter binding by T. aquaticus RNAP holoenzyme (19). At the same time, this substitution enhanced RNAP interactions with single-stranded DNA, suggesting a role for this amino acid in promoter opening (19).…”
supporting
confidence: 70%
“…
Figure 1.DNA templates used and sample EMSA. ( A ) Duplex is a truncated version of a longer promoter sequence used in earlier work (16). It lacks any DNA downstream of position +1.
…”
Section: Resultsmentioning
confidence: 99%
“…Substitutions at both positions have been found to be deleterious for promoter DNA melting (10,11,13,14), but remarkably, the Y430A substitution was also found to facilitate formation of complexes of RNAP with short model templates at low temperatures (15), suggesting an inhibitory role for the Y430 residue under some circumstances. The effects of substitutions for Y430 and W433 have been found to be cumulative (11,12,16). A substantial amount of experimental evidence supports a crucial role for the − 11A base on the non-template strand in initiating the process of promoter DNA strand separation (17–23), but not in formation of the closed complex (17).…”
Section: Introductionmentioning
confidence: 99%
“…The KMnO 4 probing protocol was exactly as described (19). Separation of the fragments generated from the unmodified DNA was accomplished by running the samples on a 10% sequencing gel.…”
Section: Methodsmentioning
confidence: 99%